2009
DOI: 10.4031/mtsj.43.4.6
|View full text |Cite
|
Sign up to set email alerts
|

AUV Sensors for Real-Time Detection, Localization, Characterization, and Monitoring of Underwater Munitions

Abstract: A B S T R A C TThis technical paper describes existing capabilities and new research results for autonomous underwater vehicles (AUVs) for use in locating, characterizing, and monitoring underwater munitions. The authors introduce advances in sensor technologies and search methods pertinent to AUV-based underwater munition mitigation operations. Results are presented from a series of trials using in situ chemical sensors to detect both conventional and nonconventional underwater munitions in real time. These t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 19 publications
0
1
0
1
Order By: Relevance
“…A number of studies have attempted to measure MCs in seawater, sediments, and organisms, and the results have been rather variable from site to site (Lotufo et al, 2017). The variability of detections as a function of distance from the target is likely due to the filamentous nature of the plumes emanating from the target (Rodacy et al, 2001;Camilli et al, 2009). One of the earliest reports of positive detection found low µg kg −1 levels of TNT and DNT in sediments near intact, live munitions in Halifax Harbor, Canada (Darrach et al, 1998).…”
Section: Organic MCmentioning
confidence: 99%
“…A number of studies have attempted to measure MCs in seawater, sediments, and organisms, and the results have been rather variable from site to site (Lotufo et al, 2017). The variability of detections as a function of distance from the target is likely due to the filamentous nature of the plumes emanating from the target (Rodacy et al, 2001;Camilli et al, 2009). One of the earliest reports of positive detection found low µg kg −1 levels of TNT and DNT in sediments near intact, live munitions in Halifax Harbor, Canada (Darrach et al, 1998).…”
Section: Organic MCmentioning
confidence: 99%
“…Furthermore, large variation within sites may be observed in detected concentrations as a function of distance from the dumped munition. Such variability is thought to be caused by the filamentous nature of the plumes emanating from the source of contamination (Rodacy et al, 2001;Camilli et al, 2009). Additionally, a recent study showed that in situ measurements of dissolution fluxes from exposed munition material in the Baltic Sea are actually lower than the majority of those reported for laboratory experiments but clearly demonstrate that there is in fact chemical release from the dumped munition to the water column albeit lower than expected (Beck et al, 2019).…”
Section: Detection Of Munition Constituents In the Environmentmentioning
confidence: 95%
“…Але і в першому, і в другому випадку без участі спеціально підготовлених водолазівсаперів [22] не обійтись, а організація їх діяльності вимагає урахування як можливостей особового складу, так і умов, в яких вони будуть виконувати поставлені завдання, а також тактико-технічних характеристик обладнання, яке стоїть на озброєнні у відповідних підрозділах. При цьому навіть використання автономних підводних апаратів, які базуються на сенсорних технологіях, застосуванні хімічних та біометричних датчиків, спирається на підводну оперативну діяльність особового складу, залученого до виявлення підводних боєприпасів [23], що також вимагає урахування фізіологічних характеристик підводників. Це ж відмічено і в [24], де показано, що гнучкість в плануванні та виконанні підводних робіт з предметами, що не вибухнули, забезпечується залученням професіоналів у проведенні підводних робіт із застосуванням відповідних спеціальних засобів, тактико-технічні характеристики яких відповідають можливостям водолазів та умовам, в яких буде здійснюватись процес підводного розмінування.…”
Section: аналіз останніх досліджень і публікаційunclassified